MEMAHAMI MAKNA HILAL MENURUT TAFSIR AL-QUR’AN DAN SAINS - Qomarus Zaman (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2022)
Interpretation of surah Al-Baqarah verse 189 which uses a method of transmission saying that the verse would describe the times predetermined by God to mankind in serve him well to explain when fasting, and pilgrimage feast. Similarly, the new moon will also indicate the prescribed period for women. Narrated by Bisyri bin Mu’adh said that Qatada once said: The Prophet Muhammad was asked one day by his people will paragraph لناسɎ واقيتɏ ƭ قل الأهلة عن ونكɎسأȻ at the time of the new moon has not yet appeared? Then the Prophet said to them; Then the Prophet said to them; Allah have it appear as what ever you know. لناسɎ واقيتɏ ƭtherefore to bring it up then he is as a sign on the start of fasting for the Muslims and for Iftar (feast) and indicates the time for those with the arrival of the rituals of Hajj and to determine the future iddahnya women. Hilal is a sign or marker clue is a unity of time and timing system consisting of day, month and year. This has been the form of a calendar (almanac, Taqwim) used easily for the benefi t of mankind in the implementation of fasting, pilgrimage, prayer time, the determination of the prescribed period and other mualamah agreement. In view of modern astronomy as Danjon, the new moon will be visible if the position of the moon within a minimum of 8 degrees in addition to the sun (the moon›s crescent cauld rot be seen closer to the sun for elongation less that 80). This opinion was never confi rmed by Muammer Dizer the International Islamic Conference in Istanbul Turkey in 1978, according to research that has been accepted by international astronomers declared that the moon looks at the position of the sun distance (angle of azimut) 80 and the position of elevation above the horizon of 50. He stated it is impossible if there is a majority opinion expressed in the following 50 positions height above the horizon can be seen with the eye. While MABIMS including Indonesia make imkan al-rukyat criteria states that the size of the moon positions can be seen at a height of 20, 30 the azimut distance elongation angle and distance when ijtimak and sunset time of 8 hours (kiteria to 20, 30 and 8 hours). MABIMS criteria is lower than the criterion Istanbul. This last criterion used Malaysia Singapore and Brunei, while Indonesia is still no difference and there is no agreement on these criteria.